Concentrations, Accumulation, and Interactions of Redoximorphic Metals (Fe, Mn) Between Other Elements in Plants Grown on Wastewater-Irrigated and Control Soils - Avci, Halim; Yaman, Mehmet (Springer International Publishing Ag, 2014)
Samples of soil and food plants were collected from wastewater-irrigated and control fields in the vicinity of Gaziantep, in southeast Turkey. The samples were analyzed for concentrations of several macro and trace elements to evaluate spatial differences and bioaccumulation. Emphasis was placed on redoximorphic metal (Mn/Fe) interactions. The plants and tissues that studied were corn (Zea mays) seeds, mint (Mentha) leaves, the vegetables eggplant (Solanum melongena L.) and pepper (Capsicum annuum L.), and tomato (Solanum lycopersicum L.) fruits. Concentrations of Mn and Fe in corn were generally lower than in the other food plants, while concentrations of Mn, Fe, and several elements in mint were higher in other plants. Except for mint, theMn deficiencies in the various plant samples can be attributed to low Mn soil concentrations and the chemical and physical characteristics of the soil. Mn concentrations in both wastewater-irrigated soils and control soilswere lower than what has been reported as an average for the Earth's crust (crustal average). There was considerable variability in the concentrations of Fe, with mint having the highest concentration (650 mg/kg) and corn the lowest (20 mg/kg). Significant positive relationships (coefficient of determination (R-2) > 0.50) were calculated between Mn and Fe in corn (R-2 = 0.83). The R-2 for tomato was 0.43, but all other relationships were much poorer for all other species. Several elements (trace and macro) demonstrated positive relationships with Mn or Fe, although there was little across-species consistency. For example, the R-2 values for bothMn and Fe correlated with Zn, P, and Mg were all > 0.80 for Z. mays, but were all < 0.10 for Mentha. The response of the members of the Solanaceae family (eggplant, pepper, and tomato) to the presence of Mn, Fe, and other soil constituents was similar in many respects, showing differences from Z. mays and, in particular, Mentha. Similarities among related plants are not surprising and would be expected given similar physiologies and metabolic pathways. Higher uptake of certain metals may be associated with the dominant form of the element in the soil matrix. The uptake of chemicals to plant tissues is influenced by the chemical and physical characteristics of the soil and species-specific factors.
Keywords: Manganese; Iron; Trace and macro elements; Plant tissue; Soil; Bioaccumulation